P11 Proton pump inhibitors are associated with reduced response to infliximab in inflammatory bowel disease. (19th June 2022) - Cartlidge, Peter; Tan, Poh Chai; Kang, Chan Keat; Fyall, Julie; Paterson, Jacqueline; Groome, Maximillian; McLean, Mairi H; Mowat, Craig
Abstract : Introduction: Infliximab is a first line treatment for moderate-severe inflammatory bowel disease (IBD). Proton pump inhibitors (PPI) are frequently over-prescribed. They modify the gut microbiome and a recent meta-analysis of randomised controlled studies identified that patients with IBD taking a PPI were less likely to achieve remission on Infliximab. This study reviews the response to infliximab at 12 months in patients with and without a concurrent PPI in NHS Tayside. Methods: Caldicott approval was granted for retrospective analysis of data from electronic patient records. Patients in NHS Tayside commencing Infliximab for IBD in 2018 and 2019 were identified from a biologic database. Data was collected on patient characteristics (age, gender, co-morbidities), disease characteristics, and concomitant thiopurine and PPI therapy. Pearson chi-squared test assessed the statistical significance of PPI use on Infliximab continuing at 12 months. Results: 55 patients with IBD commenced Infliximab during the study period. Average age 43 years (range 18-85) and 54% were male. 39 patients (71%) were on concomitant thiopurine therapy. 21 patients had ulcerative colitis, 30 Crohn's disease and 4 unclassified. 20 patients (36%) were concurrently taking a PPI for at least 8 weeks (mean age 50 years (range 21-86) and 65% female). Indications for PPI use were gastric protection whilst on prednisolone (n=11 (55%)), reflux (n=4 (20%)), gastritis (n=1 (5%)) and no recorded indication (n=4 (20%)). Equivalent number of patients were on dual immunosuppression in both groups. Concurrent PPI use was associated with a significantly greater chance of an inadequate response to infliximab (p=0.038) ( Figure 1 ). of the 5 patients on PPI and infliximab who were not in clinical remission at 12 months, 80% had Crohn's disease, 40% were male, and mean age was 54 years (range 26-76). Conclusions: This real-world data in our single centre suggests that concurrent PPI use is associated with impaired response to Infliximab. This study will benefit from a larger dataset and we continue to study the outcomes of additional infliximab cohorts, and other biologic therapies in IBD. In the interim we suggest taking a cautious approach when prescribing PPIs to IBD patients.